« Faire et se faire » ingénieur-manager - Glenn Ducouret (Éducation et Socialisation)
Engineers at work are regularly confronted with situations where productivity and socio-ecological issues are at odds. In order to rule on the resulting ethical issues and find a satisfying compromise, they mobilize their scientific knowledge but also their subjectivity. The purpose of our article is to suggest ways to understand and certify this new aspect of the engineers competencies who must, on the one hand, be able to perceive the human dimension of work more clearly and, on the other hand, provide their collaborators with benchmarks in order to better understand the challenges of CSR and adapt their practices.